DEWEY FINN'S AMBITION TO MAKE A NEW BAND IN RICHARD LINKLATER'S THE SCHOOL OF ROCK MOVIE (2003): A PSYCHOANALYTIC APPROACH - LIESTANTO , RONALD INDRA (2011)
The study is to reveal how the ambition to realize a dream becomes true reflected in the school of rock directed by Richard Linklater published in 2003. The objective of the study is to analyze the structural elements in the movie and to analyze the ambition to get a dream of the movie based on psychoanalytic approach. The object of the study is a movie the school of rock directed by Richard Linklater. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of the school of rock and the secondary data source is biography of character. The method of collecting data is documentation. The technique of analyzing data is descriptive. The results of the study are as follows. First, based on the structural analysis, Richard Linklater delivers a moral message that everybody has to realize his dream to become true in his life. And second based on the psychoanalytic analysis, Richard Linklater reflects the ambition of the man to realize his dream becoming true.